Translation style guides in translator training: Considerations for task design - Washbourne, Kelly (The Journal of Specialised Translation, 2012)
Style guides (style sheets or stylebooks) can constitute a key heuristic tool and pedagogical scaffolding in translator training environments in that they require the negotiation of situated meaning with multiple stakeholders, potentially across multiple tasks and cohorts of trainees. By their nature, they refer to precedent, other texts that condition the text at hand; in this sense they are a special kind of ever-evolving translation reference, paratext, and at times even a quasi-brief. The style guide is put forth as a contradictory, hybrid genre of the descriptive and prescriptive, preferred and mandated, and is yet an unscientific, though integral, part of quality control and quality assurance in many key translation domains and even of equal access to services in others (e.g. health care). The intersection of style guides with norms will be considered, and templates for style guide management tasks and variations—including analysing, updating, editing, and creating—will be proposed as part of the trainer's repertoire for building and integrating various subcompetences. Further research areas for translation pedagogy, including issues related to liability and compliance, are suggested.